Stress success a guide to pronunciation principles - Tan, Kim Hua; Mohammad Abdollahi Guilani (Penerbit UKM, Universiti Kebangsaan Malaysia, 2014)
This is a book on pronunciation principles in the English language. It consists of four chapters dealing with Stress, Spelling and stress patterns, Intonation and Subtleties of pronunciation